2012
DOI: 10.1371/journal.pone.0049058
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Exchanging Carbohydrates for Proteins in the Cholesterol Metabolism of Mice Fed a High-fat Diet

Abstract: Consumption of low-carbohydrate, high-protein, high-fat diets lead to rapid weight loss but the cardioprotective effects of these diets have been questioned. We examined the impact of high-protein and high-fat diets on cholesterol metabolism by comparing the plasma cholesterol and the expression of cholesterol biosynthesis genes in the liver of mice fed a high-fat (HF) diet that has a high (H) or a low (L) protein-to-carbohydrate (P/C) ratio. H-P/C-HF feeding, compared with L-P/C-HF feeding, decreased plasma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Increasing dietary protein reduces lipid accumulation in the liver ( 1 4 ) and in the adipose tissue (AT) ( 2 , 5 ) . These effects have been attributed to a reduced energy intake due to the satiating effect of proteins ( 6 , 7 ) , but it was also observed in pair-fed rats ( 8 ) and in ad libitum- fed mice ( 1 ) that a reduced fat mass can be observed without differences in energy intake.…”
mentioning
confidence: 99%
“…Increasing dietary protein reduces lipid accumulation in the liver ( 1 4 ) and in the adipose tissue (AT) ( 2 , 5 ) . These effects have been attributed to a reduced energy intake due to the satiating effect of proteins ( 6 , 7 ) , but it was also observed in pair-fed rats ( 8 ) and in ad libitum- fed mice ( 1 ) that a reduced fat mass can be observed without differences in energy intake.…”
mentioning
confidence: 99%
“…Thus, it is possible to formulate dietary recommendations based on a system biology perspective to ensure a healthy condition or to prevent and treat chronic diseases, such as CVDs, obesity, and cancer [ 103 ]. In this context, we particularly underline the importance of foodomics studies that over time have been performed on human, animals, and animal models of human diseases administered with (i) rosemary extracts rich in polyphenols [ 104 106 ] and corresponding isolated metabolite carnosol and carnosic acid [ 107 , 108 ]; (ii) red-to-blue fruit extracts rich in anthocyanins [ 109 ]; (iii) vegetable extracts rich in flavonoids [ 110 ] and isoflavones or isolated genistein, daidzein [ 111 ], and flavone [ 112 ]; (iv) green tea extracts rich in polyphenols [ 113 ]; (v) olive oil extracts rich in polyphenols [ 114 ]; (vi) fish oil extracts rich in polyunsaturated fatty acids [ 115 ]; (vii) resveratrol-containing foods [ 116 ]; (viii) inulin-containing prebiotics and isolated inulin; (ix) increased dietary protein [ 117 , 118 ]; (x) nutrients lacking normal Zn supplement [ 119 ]; (xi) augmented folate [ 120 ] and multivitamin/mineral supplement [ 121 ]. Due to the complexity of these studies, their results were often published in different articles.…”
Section: Foodomics For Elucidating Molecular Pathways Underlying Bmentioning
confidence: 99%
“…These effect of low carbohydrate, high fat and high protein diet on cholesterol homeostasis in mice was also documented. 67 Higher levels of amino acids inhibits the AKT mediated activation of SREBP thereby reducing the ux through cholesterol synthesis. The observation suggested that, higher levels of plasma amino acids under a diabetic state can help in reducing the HMG-CoA reductase ux there by reducing hypercholesterolemia.…”
Section: How a High Carbohydrate Diet Increases Cholesterol Levels? H...mentioning
confidence: 99%